Leadership Behavior: Empowerment Fosters to Changing Organization - Intarak, Choomsak (วารสารการบริหารการศึกษา มหาวิทยาลัยศิลปากร, 2016)
Changing organization is nowadays critical issue to operate the modernization. The aim is directed to learning organization (LO), however, the most important factor is leadership behavior that characterizes to the empowerment. It’s composed of the subordinate performance, to be satisfactory behaviors. Knowledge management (KM) is the key strategy composed of managing the generation of new knowledge through learning,capturing knowledge and experience, sharing and communicating, organizing information for easy access, and using the building on what is known. Transformational leadership is indicated that the behaviors supported to develop subordinates and fostered to organizational change. In a changing society at the present time, it needs the development of persons and society, however, the influence for change is that the leadership behavior. It means that the development in change agent should be emphasized on leader behavior to be empowerment which composed of intelligence power, creative thinking, decision making, and technical skills. These characteristics imply to the organizational change. The empowerment for the leader is to provide and nurture the necessary skills and understanding required of leader by teaching, coaching, and mentoring process. In this mention is implied to the individuals in organization must be leadership by empowerment with knowledge management that will foster to the organizational change.